Implementation of antireflection layers for improved efficiency of carbon nanotube–silicon heterojunction solar cells. (August 2015) - Yu, LePing; Tune, Daniel D.; Shearer, Cameron J.; Shapter, Joseph G.
Highlights: The polymer antireflection layers can increase the energy absorbed by the silicon in a Si–CNT solar cell. The polymer antireflection layers can enhance the performance of Si–CNT cells. The thickness of the polymer layer has an influence on the level of performance improvement observed. The polymer antireflection layer can reduce the degradation of Si–CNT cells. Abstract: We explore the use of antireflection polymer layers on n-type silicon solar cells that use a carbon nanotube (CNT) front electrode. Three different types of polymer were studied; polydimethylsiloxane (PDMS), poly(methyl methacrylate) (PMMA) and polystyrene (PS). The influence of polymer type and thickness on device performance has been assessed. The performance degradation with ageing of Si–CNT, Si–CNT–PDMS, Si–CNT–PMMA and Si–CNT–PS solar cells has been compared. Based on the analysis of the results, antireflection polymer layers are able to reduce the reflectance of the cell surface and subsequently improve the amount of solar energy absorbed by the silicon without any detrimental effect on the photovoltaic junction. With the addition of a 75 nm PS antireflection layer, devices achieved a photovoltaic conversion efficiency of up to 7.8% under standard AM 1.5G conditions.